Optimod’s Improving Entrepreneurial Journey Initiative (IEJI): Bridging the Gap between Theory and Practice in Entrepreneurial Ecosystem Development - Kremsar, Sara; Marič, Miha (Improving Entrepreneurial Journey, 2025)
The Optimod Improving Entrepreneurial Journey Initiative (IEJI) is a continuous research-based project developed and led by Optimod since 2022 to explore the relationship between theoretical entrepreneurship studies and practical experience. Conducted annually, the initiative gathers insights from more than one hundred global founders, CEOs, and leaders, highlighting their real-world experiences and strategic reflections that reveal the complexities of entrepreneurship. Its purpose is to establish a structured framework for understanding how knowledge transfer, leadership development, and collaborative learning contribute to entrepreneurial success. Using a mixed-methods approach that combines surveys, expert interviews, and case studies, the research identifies key factors influencing entrepreneurial growth, including mindset development, innovation, and resilience. Each year, the findings are synthesized into a comprehensive publication that merges academic reflection with practical guidance. The results highlight the importance of human-centric and ecosystem-based approaches that connect education, practice, and sustainable business development. The initiative contributes to the academic field of entrepreneurship by providing a long-term, replicable model that bridges theory and practice while supporting inclusive, adaptive, and innovation-driven entrepreneurial ecosystems.